Empowering Asynchronous Arabic Language Learning Through PDF Hyperlink Media - Riwanda, Agus; Ridha, Muhammad; Islamy, M. Irfan (International Review of Research in Open and Distributed Learning, 2024)
The migration to online learning has brought about several new problems. Poor signal quality, large Internet quotas, and device compatibility with learning applications are the most common complaints among students. Additionally, students’ poor self-directed learning skills, the excessive number of assignments given by teachers, and the use of monotonous teaching methods and media are also identified as issues. Therefore, the development of learning media that facilitate students’ learning processes and support their active engagement becomes crucial. This research aimed to develop PDF hyperlink learning media for online Arabic language learning at Madrasah Aliyah Negeri 4 in Hulu Sungai Tengah District, South Kalimantan, Indonesia (MAN 4 HST). The research model used in this study is the 4D model, consisting of four stages: define, design, develop, and disseminate. In this research, layout and accessibility received good validation scores of 4.3, and the presentation of the contents received a good validation score of 4.2. Additionally, the Wilcoxon test results indicated that the use of PDF hyperlink media significantly influences learning outcomes and receives positive feedback from students. Thus, the use of PDF hyperlink media is recommended for educational institutions experiencing digital divides, as well as those implementing asynchronous learning.